Breve introducción al neoconstitucionalismo andino para europeos. Posibilidades e imposibilidades - Carlos De Domingo Soler (Universidad Hemisferios, 2020)
Recently, the tenth anniversary of the current Ecuadorian and Bolivian constitutions was celebrated. In them, the influence of the core ideas of the Andean Neoconstitutionalism is evident. This paper tries to look for the differences between the Andean Neoconstitutionalism and the Spanish Constitutionalism, finding the justification in alternative and creative solutions that the production of Andean theory has proposed to legal and political problems shared with Spain. This article created by legal comparative and interdisciplinary methodologies may not only raise legal interest but also political. The first argument is about the paradox between law and politics with the Andean Neoconstitutionalism. Second, I describe concisely the concept of pluriversality that allow us to detach ourselves from Eurocentric bias. Finally, I compare the fundamental aspects of the Andean Neoconstitutionalism and the Liberal European Constitutionalism –Plurinationalism, Multiculturalism, Interlegality and Nature–. We will conclude that in spite of the great differences between indigenous cosmovision and European Christian tradition, there are several important similarities between our national problematics, especially in plurinational, multicultural and interlegal issues. Although, a priori it seems impossible to implement the Andean ideas into the Spanish society.